Kajian Pola Ornamen (Ragam Hias) Bernuansa Melayu untuk Fasade Bangunan Publik di Kota Pontianak - wahyudin ciptadi; Erwin Rizal Hamzah; Dewi Ria Indriana (Vokasi, 2020)
There is a phenomenon in the Regional Government of Pontianak City in realizing a public building facade, especially office functions that have a local identity value, which are required to apply the use of distinctive local ornaments (ornaments). One of the local ornaments (decorations) that will be used in public buildings in Pontianak is the Pontianak Malay nuances. The use of local ornaments (ornaments) that are applied in public buildings in the city of Pontianak is heavily influenced by elements found in traditional Pontianak Malay houses and from the Pontianak Kadriah Palace.The determine benchmarks aspects in discussing the study of ornamental patterns in a building, namely by using a model system (stylistic system) from the theory of N.J. Habraken (1978). System model (stylistic system) is a method used to determine benchmarks related to style or style including facades, door and window shapes and ornamental elements (decoration) both in the upper (head), middle (body) elements. ), and elements of the bottom (foot) of the building. In this applied research, the object of his research is the pattern of ornaments (decorative styles) with Pontianak Malay nuances used in traditional Pontianak Malay houses and the Pontianak Kadriah Palace. This applied research aims to compile and study a database of Pontianak Malay nuances of ornamental patterns so that they can be used for the design of public buildings in Pontianak, especially office functions. This applied research uses a rationalistic-qualitative approach by taking several research samples from the Pontianak Kadriah Palace and the population of traditional Pontianak Malay houses that are in 3 (three) communality zones. This study uses several stages of the implementation process, namely: the data collection stage (initial observation, follow-up observation, and interviews) and the data analysis stage and discussion of the research results. The expected result of this applied research is the compilation and documentation of a database of ornamental patterns with Pontianak Malay nuances that can be used for the design of public building facades in Pontianak, West Kalimantan.